(untitled) (Swiss Medical Weekly, 2015)
BACKGROUND:Pulseless electrical activity (PEA) cardiac arrest is characterised by a residual organised electrical activity. PEA is frequently induced by reversible conditions. The mnemonic “4H&4T” was proposed as a reminder to assess for Hypoxia, Hypovolaemia, Hypo/Hyperkalaemia, Hypothermia, Thrombosis, cardiac Tamponade, Toxins, and Tension pneumothorax. Other potential aetiologies have been identified, but their respective probability and frequencies are unclear. The aim of this study was to analyse the aetiologies of PEA out-of-hospital cardiac arrests and to evaluate their relative frequencies. METHODS: This was a retrospective study based on data routinely and prospectively collected. All adult patients with PEA as the first recorded rhythm and admitted between 2002 and 2012 to the emergency department (ED) after return of spontaneous circulation or under resuscitation were included. RESULTS: A total of 1,866 out-of-hospital cardiac arrests were included. PEA was the first recorded rhythm in 232 adult patients (12.4%) and 144 of these were admitted to the ED. The mean age was 63.8 ± 20.0 years, 58.3% were men. The survival rate at 48 hours was 29%. Hypoxia (23.6%), acute coronary syndrome (12.5%) and trauma (12.5%) were the most frequent causes. We were unable to identify a specific cause in 17.4%. Pulmonary embolism, hypovolaemia, intoxication and hypo/hyperkalaemia occurred in fewer than 10% of the cases. Nonischaemic cardiac disorders and intracranial haemorrhage occurred in 8.3% and 6.9%, respectively. CONCLUSIONS: Intracranial haemorrhage and nonischaemic cardiac disorders represent significant causes of PEA, with a prevalence equalling or exceeding the frequency of classical 4H&4T aetiologies. These conditions are potentially accessible to simple diagnostic procedures (computed tomography or echocardiography).